2021
DOI: 10.1186/s41476-021-00155-w
|View full text |Cite
|
Sign up to set email alerts
|

Stimulated Raman scattering simulation for imaging optimization

Abstract: Two simulation programs of a stimulated Raman scattering microscopy (SRS) imaging system with lock-in amplifier (LIA) detection were developed. SRS is an imaging technique based on the vibrational Raman cross-section as the contrast mechanism and enables fast, label-free imaging. Most SRS implementations are based on LIA detection of a modulated signal. However, building and operating such SRS set-ups still poses a challenge when selecting the LIA parameter settings for optimized acquisition speed or image qua… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Each SRS measurement was conducted over the whole injection time of 20 min with a 60.5 μs acquisition time. For the lock-in amplifier (LIA) settings, a time constant of 13 μs and a filter order of 8 were chosen to support this time resolution . For the detection in epi-mode, the laser power at the sample was set to 33 mW for the 1064 nm beam (Stokes) and 17 mW for the OPO output beam (pump), whereas for detection in transmission mode, the laser powers were set to 66 and 34 mW, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Each SRS measurement was conducted over the whole injection time of 20 min with a 60.5 μs acquisition time. For the lock-in amplifier (LIA) settings, a time constant of 13 μs and a filter order of 8 were chosen to support this time resolution . For the detection in epi-mode, the laser power at the sample was set to 33 mW for the 1064 nm beam (Stokes) and 17 mW for the OPO output beam (pump), whereas for detection in transmission mode, the laser powers were set to 66 and 34 mW, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…The LIA mixes the detected signal with a reference frequency used for the Stokes beam modulation and applies a low pass filter. The result is a DC signal proportional to the amplitude of the detected signal (pump beam) modulation, i.e., the SRS signal . Although SRS has been applied successfully for the analysis of microplastics on a filter, in a silicone tissue phantom, and in suspension, , the detection of plastic particles below 1 μm (NPLs) with SRS has not been demonstrated so far.…”
Section: Introductionmentioning
confidence: 99%
“…More detailed information can be found in a publication by Zada et al , who describe the effects of various lock-in amplifier settings on SRS signal and image formation, and their freely available simulation programme for SRS imaging. 35…”
Section: Instrumentationmentioning
confidence: 99%
“…In the literature of SRS, great attention is given to technological and application advances, while the investigations of noise are often overlooked, although SNR is a crucial issue not only for biological imaging, but also for spectroscopic applications [25,26]. The hardware characterizations, usually, are carried out to assess the shot noise condition [27][28][29][30][31][32]. A systematic study of SRS noise was reported in ref.…”
Section: Introductionmentioning
confidence: 99%